Predatory potential of Cryptolaemus montrouzieri Mulsant on mealybugs and aphids - Surwase, S. R.; S. S., Shetgar; S. H., Timke (Journal of Biological Control, 2021)
The predatory potential of Cryptolaemus montrouzieri Mulsant on mealybugs and aphids viz, Maconellicoccus hirsutus, Phenacoccus solenopsis and Aphis gossypii was studied at the Biocontrol Agents Laboratory, Department of Agricultural Entomology, College of Agriculture, Latur at the temperature of 25±2°C maintained in BOD incubator during year 2013-14. The consumption rate of grubs and beetles of C. montrouzieri was in order of A. gossypii>M. hirsutus>P. solenopsis.